« Ambassadors of democracy » : les soldats de l’armée d’occupation des États-Unis en Allemagne (1945-1949) - Myriam Chasserieau (Caliban: French Journal of English Studies)
In the spring of 1945, the United States, the United Kingdom, the Soviet Union and France assumed supreme authority in Germany. The American occupation policy provided for an "affirmative program of reorientation … designed completely to eliminate Nazi and militaristic doctrines and to encourage the development of democratic ideas." The American soldiers, as "ambassadors of democracy" and "America's best salesmen," became key actors in the reorientation process. Army materials emphasized that soldiers were given a fulfilling mission which consisted in making victory stick. The troop information program encouraged servicemen to promote democracy in their informal contacts with Germans. Soldiers and their dependents had to display a friendly face of hard power and exert soft power influence. In 1946, the Army devised a comprehensive program for German youth—the Army Assistance to German Youth Activities (GYA)—designed to reduce juvenile delinquency and demonstrate democratic concepts. Sports activities were regarded as an effective tool to reach German children's thinking and teach democratic values of fair play and teamwork. In the midst of Cold War tensions, sports activities were also utilized to expose Germans to American culture and traditions.